Management of breakthrough pain due to cancer[Polish version: Bóle przebijające u pacjentów z chorobą nowotworową p. 502] - Rudowska, Joanna (Contemporary Oncology/Współczesna Onkologia, 2012)
Breakthrough pain is defined as the transient exacerbation of pain occurring in a patient with otherwise stable, persistent pain. It is estimated to affect over 50% of patients, particularly those with moderate to severe background pain. Breakthrough pain is one of the most difficult pain syndromes to treat. There are several types of breakthrough cancer pain: incidental type involves flares of pain associated with movement or activity; idiopathic type is transitory pain unrelated to a specific activity; and in end-of-dose failure pain occurs when blood levels of medications fall below an analgesic threshold at the end of a dosing interval. Persistent and breakthrough pain are distinct components of cancer pain and require separate management. Successful management of breakthrough pain may require a combination of pharmacological and non-pharmacological treatment strategies. Supplemental analgesia, known as rescue medication, is a common pharmacological treatment option. Breakthrough pain is treated with supplemental short-acting opioid use, as needed, e.g. short-acting morphine, intranasal fentanyl and buccal tablets of fentanyl.